Home Literacy Practices in Early Education: A Qualitative Case Study of Grade 1 School Children and Teacher Insights - Xoliswa Patience Magxala; Joseph Baidoo (E-Journal of Humanities, Arts and Social Sciences)
South Africa has a complex educational landscape. This study explored four children’s early home literacy practices and their uptake by Grade 1 teachers in rural Libode, Eastern Cape Province in South Africa. The paper addresses the critical need for understanding literacy development in multilingual, resource-constrained environments. Using a qualitative, ethnographic design underpinned by Cultural Historical Activity Theory (CHAT), the study used observations and interviews in home and school settings. The findings revealed a rich diversity of home literacy practices, including oral traditions and emerging digital literacy, contrasting with the school’s emphasis on phonics-based instruction and English as the language of learning. Significant disparities between home and school practices challenge children’s educational transition. Evidence of translanguaging suggests a potential for multilingual approaches to instruction. The study contributes valuable insights for developing culturally responsive pedagogies, informing teacher training, and guiding resource allocation to enhance literacy outcomes in South Africa’s Foundation Phase.